From individual to community: issues in development studies : essays in memory of Malcolm Adiseshiah - Maria Saleth, R, Ed; Adiseshiah, Malcolm S. (Sage Publications India Pvt. Ltd., 2012)
Malcolm S. Adiseshiah, Indian development economist; contributed articles.